OP0270 Osteoporotic Hip Fractures in Extreme Elderly Men: A Growing Problem. (23rd January 2014) - Sehgal, A.; Mithal, A.; Mannalithara, A.; Singh, G.; Triadafilopoulos, G.
Abstract : Background: Extreme elderly (EE or >80 years) men are the fastest growing segment of population due to rapid declining cardiovascular mortality and better medical care. There is little epidemiologic data on osteoporotic hip fractures in EE men compared to women even though EE will form more than 25% of US population by 2050. Objectives: To study trends in osteoporotic hip fracture hospitalizations in the EE men and women from 1993 to 2008. Methods: We examined all EE hospitalizations in Nationwide Inpatient Sample (NIS) from 1993 to 2008 with a diagnosis of non-traumatic (osteoporotic) hip fractures. The NIS is a stratified random sample of all US community hospitals and includes data on over 37.5 million hospitalizations per year. Results: We studied 2.88 million osteoporotic hip fracture hospitalizations in 150.98 million person-years (PY) of observation in EE individuals from 1993 to 2008. Of these, 2.26 million hip fractures occurred in 99.8 million EE women-years of observation and 626, 000 occurred in 51 million EE men-years of observation. Hip fracture hospitalizations in EE women decreased from 136, 956 in 1993 (2, 618 per 1, 000 PY) to 136, 494 in 2008 (1, 874 per 1, 000 PY), even as the population of EE women increased by 39% from 5.2 million in 1993 to 7.2 million in 2008 perhaps reflecting increasing awareness, screening and treatment for osteoporosis in elderly women. However, in EE men, hip fracture hospitalizations increased from 35, 252 in 1993 to 43, 934 in 2008, even as the prevalence (per 1000 PY) decreased from 1, 427 in 1993 to 1, 100 in 2008. This increase in hip fracture hospitalizations, in spite of decreasing prevalence is coincident with the dramatic rise in the number of the EE men, from 2.47 million in 1993 to 3.99 million in 2008 (61.6% increase). Image/graph: Conclusions: Osteoporotic hip fractures pose a growing problem in the EE, more so than older adults, increasing their risk for hospitalization, morbidity and mortality greatly. Despite an overall decrease in prevalence, the absolute number of osteoporotic hip fractures continues to increase in EE men since significantly more men are living past their 80 th year of life. Aggressive measures towards recognition, prevention and therapy of osteoporosis during the medical care of EE, both ambulatory and in assisted living facilities is needed. Disclosure of Interest: None Declared